Scale-up approach for supercritical fluid extraction with ethanol–water modified carbon dioxide on Phyllanthus niruri for safe enriched herbal extracts - Norsyamimi Hassim (Nature Portfolio, 2021)
Abstract Scaling-up supercritical fluid extraction (SFE) for the extraction of bioactive compounds from herbal plants is challenging, especially with the presence of alcohol-water as co-solvent. Hence, the main objective of this study is to validate the scale-up criteria of SFE process for Phyllanthus niruri (P. niruri), and analyse the extract safety and profitability process at the industrial scale. The study was performed by using supercritical carbon dioxide (SC-CO2) with ethanol–water co-solvent at two operating conditions (L1: 200 bar, 60 °C and L2: 262 bar, 80 °C). The solvent-to-feed ratio (S/F) scale-up validation experiments were conducted at both operating conditions with feed mass capacity of 0.5 kg. The extraction yields and overall extraction curves obtained were almost similar to the predicted ones, with error of 5.13% and 14.2%, respectively. The safety of scale-up extract was evaluated by using a toxicity test against zebrafish embryo (FETT). The extract exhibited a low toxic effect with the LD50 value of 505.71 µg/mL. The economic evaluation using a detailed profitability analysis showed that the SFE of P. niruri was an economically feasible process, as it disclosed the encouraging values of return on investment (ROI) and net present values (NPV) for all scale-up capacities.